2010
DOI: 10.1080/17446540802599671
|View full text |Cite
|
Sign up to set email alerts
|

The empirical determinants of target capital structure and adjustment to long-run target: evidence from Canadian firms

Abstract: The main objective of this article is to provide more insight into the empirical determinants of target capital structure of Canadian firms. Panel data covering the period 1996 to 2004 was analysed using a much stronger estimation technique, that is, a dynamic regression model. The results show that profitability and tangibility have a positive and significant impact on the firm leverage, whereas growth opportunities and size have a negative influence on the leverage of Canadian firms. The study also suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 38 publications
15
57
0
Order By: Relevance
“…The information asymmetry argument discussed earlier should plausibly explain the negative association. The negative association between size and leverage is confirmed in several other studies (Chen, 2004;Delcoure, 2007;Nunkoo & Boateng, 2010).…”
Section: Sizesupporting
confidence: 75%
“…The information asymmetry argument discussed earlier should plausibly explain the negative association. The negative association between size and leverage is confirmed in several other studies (Chen, 2004;Delcoure, 2007;Nunkoo & Boateng, 2010).…”
Section: Sizesupporting
confidence: 75%
“…While Couto and Ferreira (2010) and Chadha and Sharma (2015) assert that tangibility is a determinant factor of capital structure, Nunkoo and Boateng (2010) argue that tangibility has a positive influence on leverage.…”
Section: Tangibilitymentioning
confidence: 99%
“…However, some studies have concluded otherwise, which might be a consequence of using different variables for growth, such as net assets growth rate (Couto & Ferreira 2010;Rebelo 2006), total assets growth rate (Chang et al 2009;Nunkoo & Boateng 2010) or speed of adjustment (Oinoa & Ukaegbu 2015). Sbeiti (2010) argues that growth needs to be defined through the following ratio: total assets book value minus net assets book value and the market value of equity over the total assets book value.…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Flannery and Rangan (2006) showed that nonfinancial companies identify and tend to reach an indebtedness target ratio very quickly for the period 1966-2001. More recently, Nunkoo and Boateng (2010) established that long term leverage of Canadian firms would tend to an indebtedness target ratio event if the adjustment were relatively slow.…”
Section: From the Fundamentals Of Financial Behaviour To The Static Tmentioning
confidence: 99%